Does Donor Allograft Microsteatosis Matter? Comparison of Outcomes in Liver Transplantation With a Propensity‐Matched Cohort. Issue 10 (8th July 2019) - Croome, Kristopher P.; Lee, David D.; Croome, Sarah; Nakhleh, Raouf E.; Abader Sedki Senada, Peter; Livingston, David; Yataco, Maria; Taner, C. Burcin
Abstract : It has been suggested that microsteatosis does not negatively impact graft survival following liver transplantation (LT). The present study represents the largest series on donor livers with significant microsteatosis and investigates the impact of microsteatosis on perioperative factors such as postreperfusion syndrome (PRS), early allograft dysfunction (EAD), and postoperative renal dysfunction. Clinical outcomes of all patients undergoing LT with donor livers with isolated microsteatosis (≥30%; n = 239) between 2000 and 2017 were compared with a propensity score–matched cohort of patients undergoing LT with donor livers with no steatosis (n = 239). Patients in the microsteatosis group had a higher rate of PRS (33.1% versus 24.2%; P = 0.03), EAD (38.2% versus 23.0%; P < 0.001), and continuous renal replacement therapy (CRRT) requirement following LT (10.9% versus 3.6%; P = 0.002) than the no steatosis group. No difference in patient ( P = 0.33) or graft survival ( P = 0.18) was observed between the 2 groups. On multivariate regression, livers with microsteatosis had an increased risk of graft loss with retransplant recipients (hazard ratio [HR], 1.59; P < 0.001), increasing Model for End‐Stage Liver Disease (MELD) score (HR, 1.13; P = 0.01), and organs from donation after circulatory death donors (HR, 1.46; P = 0.003). In conclusion, recipients of donor livers with significant microsteatosis are at an increased risk of PRS, EAD, and postoperative renal dysfunction requiring CRRT. Livers with significant microsteatosis should be avoided in retransplant recipients and in recipients with high biological MELD scores. Once appropriately selected recipients of these livers are able to overcome the initial perioperative implications of using these donor livers, longterm patient and graft survival is similar to recipients receiving grafts with no steatosis.